2019
DOI: 10.1016/j.tsf.2019.137479
|View full text |Cite
|
Sign up to set email alerts
|

A review of the intrinsic ductility and toughness of hard transition-metal nitride alloy thin films

Abstract: Over the past decades, enormous effort has been dedicated to enhancing the hardness of refractory ceramic materials. Typically, however, an increase in hardness is accompanied by an increase in brittleness, which can result in intergranular decohesion when materials are exposed to high stresses. In order to avoid brittle failure, in addition to providing high strength, films should also be ductile, i.e., tough. However, fundamental progress in obtaining hard-yet-ductile ceramics has been slow since most toughe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(39 citation statements)
references
References 167 publications
3
33
0
Order By: Relevance
“…A further increase in testing temperature decreases the average friction coefficient; the minimum average friction coefficient is 0.29 at 550 °C. Similar friction properties were also reported in other transition metal nitride films, such as TiAlVN [22], ZrAlN [23], and W-Si-N [5]. Figure 4 also presents the wear rate as a function of various testing temperatures.…”
Section: Tribological Propertiessupporting
confidence: 77%
See 2 more Smart Citations
“…A further increase in testing temperature decreases the average friction coefficient; the minimum average friction coefficient is 0.29 at 550 °C. Similar friction properties were also reported in other transition metal nitride films, such as TiAlVN [22], ZrAlN [23], and W-Si-N [5]. Figure 4 also presents the wear rate as a function of various testing temperatures.…”
Section: Tribological Propertiessupporting
confidence: 77%
“…It can be clearly observed that the testing temperature has a significant effect on the average friction coefficient. When the testing temperature is below 200 • C, the average friction coefficient increases from 0.30 at 25 • C to 0.53 at 200 • C. A further increase in testing temperature decreases the average friction coefficient; the minimum average friction coefficient is 0.29 at 550 • C. Similar friction properties were also reported in other transition metal nitride films, such as TiAlVN [22], ZrAlN [23], and W-Si-N [5]. Tribo-film is known to significantly influence the tribological properties of transition metal nitride films, since tribo-oxidation has been reported to be a generalized phenomenon [6,7,11].…”
Section: Tribological Propertiessupporting
confidence: 73%
See 1 more Smart Citation
“…[39][40][41] Besides, TMN has a typical technical approach along with interesting mechanical properties. 42 The superior mechanical performance of TMNs is critical for the long-term life span of energy storage devices, making it favorable. The excellent mechanical support will mitigate the volume change during the reaction, where it will decrease the pulverization and stabilize the entire electrode.…”
Section: Transition Metal Nitridesmentioning
confidence: 99%
“…43 It shows high volumetric capacitances and great cycling life as well as high rate of capability. 42 Besides, the raw materials for metal nitrides are lower in properties indicating that TMN is now a significant field of supercapacitor electrode materials. 44,45 The basic potential of metal nitrides is more significant in action compared to carbon and polymers.…”
Section: Transition Metal Nitridesmentioning
confidence: 99%